Notary Public's Responsibility for Self-Promotion Practices Through Social Media Reviewed from the Notary Code of Ethics and the Notary Law - Areta, Azzahra Lintang; Darmadi, Nanang Sri; Hasana, Dahniarti (TABELLIUS: Journal of Law, 2026)
A notary is a public official authorized to create authentic deeds. Therefore, all activities undertaken by a public official must comply with existing regulations. Notaries are governed by the Notary Code of Ethics and the Notary Law. One important provision within these provisions prohibits self-promotion through social media. The purpose of this study is to determine the legal consequences of notary promotion through social media and to understand the process of handling notary promotion through social media codes of ethics, as reviewed by the Notary Code of Ethics and the Notary Law. To achieve the research objectives, the author employed a normative legal research method, which utilizes library materials as primary data for case analysis without conducting fieldwork. This type of research is also known as research that focuses on the study of legal principles, legislation, and relevant legal literature. The research results show that examples of actions taken by notaries as a form of self-promotion through social media are through websites, social media (TikTok, Instagram), webinars, and seminars. In addition, Article 4 paragraph 3 of the Notary Code of Ethics also states that notaries are prohibited from conducting self-promotion in any form, including through social media. Therefore, legal consequences for notaries who continue to promote themselves through social media will be subject to sanctions based on violations of the Notary Code of Ethics and the Notary Law. The process of handling violations of the notary promotion code of ethics on social media involves supervision by two institutions: the Honorary Council and the Supervisory Board. The Honorary Council's main task is to supervise the implementation of the Notary Code of Ethics. Meanwhile, the Supervisory Board not only supervises the implementation of the Notary's job duties to ensure they comply with the provisions of the Notary Law, but also the Notary Code of Ethics and the Notary's behavior or life behavior.